Analisis Pelatihan Kerja, Kepuasan Kerja Dan Kompensasi Terhadap Kinerja Personil Satuan Polisi Pamong Praja (POLPP) Kabupaten Padang Pariaman - Lenny Hasan; Henny Sjafitri; Rosyiidah Mardhiyyah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this research is to determine and analyze the influence of job training, job satisfaction and compensation on the performance of Padang Pariaman Regency Civil Service Police Unit (Pol PP) personnel. The research method is descriptive quantitative. The population was 37 people. A sample of 37 people was taken using total sampling technique. Data analysis techniques are multiple linear regression, t test, F test and coefficient of determination. The results of multiple linear regression analysis are Y = 2.701 + 0.036 X1 + 0.301 X2 + 0.223 X3 + e. The results of the t test found that job training had no effect on the performance of Padang Pariaman Regency Civil Service Police Unit (Pol PP) Personnel and job satisfaction and compensation had a positive and significant effect on the performance of Padang Pariaman Regency Civil Service Police Unit (Pol PP) Personnel. The results of the F test found that job training, job satisfaction and compensation together had a positive and significant effect on the performance of Padang Pariaman Regency Civil Service Police Unit (Pol PP) personnel. The results of the coefficient of determination test found that the variable ability of job training (X1), job satisfaction (X2) and compensation (X3) explained the personnel performance variable (Y) by 65.9% and the remaining 34.1% was explained by other variables not discussed in the this research. Keywords: Job Training, Job Satisfaction, Compensation, Personnel Performance.